A taxa de performance e o comportamento de risk shifting dos fundos de investimento em ações - Althaus Junior, Adalto Acir (2017)
This study aims to investigate the risk shifting behavior of mutual funds to test the hypotheses that managers have incentives to raise risk. We evaluated the effect of performance fees on the level of risk, risk shifting and mutual fund's performance to assess agency costs differences between both mutual funds - with and without performance fees. We observed the mutual fund's volatility level and its changes imposed by the managers. Volatility was estimated by a standard deviation of returns in the last 12 months. The change on the level of risk measured was the risk shifting, that is, the difference between a mutual fund's current portfolio holdings volatility and its past realized volatility, both estimated over past 12 months' period. We used a sample of 203 Brazilian mutual funds which covered the period from 2009 to 2015. We used data from stock prices, Brazilian bonds prices, BDRs prices and the characteristics of these funds. When funds have higher monthly returns, they tend to run negative risk shifting; when they have lower monthly returns, they tend to seek risk by doing positive risk shifting. When the funds decrease their risk (negative risk shifting), they tend to perform better. It is possible to ensure that the funds which charge performance fee have superior performance if compared to those that without performance fee. Also, they have greater positive risk shifting and lower negative risk shifting. However, funds that charged performance fees presented lower levels of risk. These findings suggest that the performance fee can contribute to align interests between mutual funds and their investors. These results are more in accordance to the behavior of risk-averse managers who used their stock selection or market timing ability to ensure a desirable minimum performance, rather than use maximum effort to looking for extraordinary returns.